The Effect of Salicylate Compounds on K. pneumoniae pneumoniae Isolated from Different Clinical Infections - الملا حوراء; ملكونيان اليس; شوكت سهام (Iraqi Journal of Science, 2025)
The effect of Salicylate compounds against Klebsiella pneumoniae pneumoniae was studied by using different concentrations of Acetylsalicylic acid (ACSA), Salicylic acid (SA) and Sodium salicylate (SS). Reduction of capsular polysaccharide (CPS) production increased with the increment of Salicylate compounds concentrations.Transmission electron microscopy study showed that the average thickness of CPS for untreated bacteria with Salicylate compounds was 245 nm while 63.5 nm, 54.3 nm and 50 nm for the bacteria treated with 300 μg/ml of ACSA, SA and SS respectively, with reduction percentages of CPS 74.08%, 77.83% and 79.59% respectively. The results of testing the effect of Salicylate compounds on antibiotics sensitivity (Amoxiclave, Cefotaxime, Amikacin ,Ciprofloxacin and Doxycyclin) revealed that the activity of Amoxiclave and Cefotaxime were not affected when MIC values were not changed. However, Amikacin activity increased when MIC values decreased to 2 - 4 folds, while Ciprofloxacin and Doxycyclin activity decreased when MIC values increased to 2 – 4 folds. The results regarding the effect of Salicylate compounds on the adhesion of K. pneumoniae pneumoniae on human epithelial cells showed mild decrease in the number of adhered cells in some of the isolates, with non-significant differences between the treated and untreated bacteria for all compounds. Yet, the differences were significant (P<0.01) between the adherence of resistant and sensitive isolates to antibiotics, hence the adherence ability of the sensitive isolates was weaker than the resistant ones.The effect of Salicylate compounds on phagocytic activity of the polymorphnuclearleukocytes toward K. pneumoniae pneumoniae was demonstrated by the increase inthe phagocytic index and percent phagocytosis. The differences were significant(P<0.01) between the untreated and treated bacteria with 300 μg/ml of ACSA, SAand SS .